1994
DOI: 10.1530/eje.0.1310369
|View full text |Cite
|
Sign up to set email alerts
|

Changes in calciotrophic hormones and biochemical markers of bone turnover in normal human pregnancy

Abstract: Plasma concentrations of parathyroid hormone-related protein (PTHrP), parathyroid hormone, alkaline phosphatase, osteocalcin and albumin-adjusted calcium were measured along with nephrogenous cyclic adenosine monophosphate (NcAMP) in 10 normal women longitudinally through pregnancy. In addition, an assessment of bone resorption was made in these same subjects by the measurement in true fasting urine specimens of the calcium/creatinine ratio (Ca/Cr), hydroxyproline/creatinine ratio (HP/Cr), pyridinoline/creatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
62
1
5

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(78 citation statements)
references
References 0 publications
10
62
1
5
Order By: Relevance
“…Our present results, together with the findings of others (16,23,26), have not confirmed the pregnancyassociated increases in PTH that have been reported previously. Intact-PTH concentrations tended to decrease during the course of pregnancy, but to increase postpartum, suggesting a state of 'secondary hyperparathyroidism' that may prevail to compensate for the transfer of calcium into the mammary glands for milk production (Fig.…”
Section: European Journal Of Endocrinology (1997) 137contrasting
confidence: 93%
See 2 more Smart Citations
“…Our present results, together with the findings of others (16,23,26), have not confirmed the pregnancyassociated increases in PTH that have been reported previously. Intact-PTH concentrations tended to decrease during the course of pregnancy, but to increase postpartum, suggesting a state of 'secondary hyperparathyroidism' that may prevail to compensate for the transfer of calcium into the mammary glands for milk production (Fig.…”
Section: European Journal Of Endocrinology (1997) 137contrasting
confidence: 93%
“…The stimulus for the increase in calcitriol during pregnancy remains unknown, however. It seems to be unrelated to serum PTH, as the concentrations of intact-PTH were found to decrease with advancing gestation in our pregnant women, which is consistent with several earlier findings (16,(23)(24)(25)(26). In addition, an increase in intact-PTH concentrations postpartum paralleled a decrease in the concentrations of calcitriol (Figs 1 and 2), thus the increase in PTH postpartum did not result in further synthesis of calcitriol -an expected stimulus for enhanced calcium absorption.…”
Section: European Journal Of Endocrinology (1997) 137supporting
confidence: 91%
See 1 more Smart Citation
“…Biochemical markers of the maternal bone turnover indicate that bone remodeling is low during the first half of the pregnancy and may increase in the third trimester (5,6,7). Fibroblast growth factor 23 (FGF23) is expressed predominantly in osteoblasts and osteocytes (8).…”
Section: Introductionmentioning
confidence: 99%
“…This increase of 1,25(OH) 2 D is independent of a rise in maternal PTH which remains in the low-normal range in the 1 st trimester 43,[66][67][68][69] . Studies have shown that that CYP27B1 activity can be regulated by other sources including parathyroid hormonerelated protein (PTHrP), oestradiol, prolactin (PRL) and placental lactogen [70][71][72] , all of which are increased in pregnancy and which may help explain the rise in 1,25(OH) 2 D independent of PTH responses.…”
Section: Vitamin D and The Regulation Of Mineral Homeostasis During Pmentioning
confidence: 79%